A Critical Study on Chalukya Dynasty: A Historical Analysis of the Chalukya Dynasty and its Influence on Southern and Central India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The Chalukya dynasty was an Indian royaldynasty that ruled large parts of southern and centralIndia between the 6th and the 12th centuries.During this period, they ruled as three related yet individual dynasties. Theearliest dynasty, known as the "Badami Chalukyas", ruled from Vatapi(modern Badami)from the middle of the 6th century. The Badami Chalukyas began toassert their independence at the decline of the Kadamba kingdomof Banavasi andrapidly rose to prominence during the reign of Pulakesi II.After the death of Pulakesi II, the EasternChalukyas became an independent kingdom in the eastern Deccan. They ruledfrom Vengi untilabout the 11th century. In the western Deccan, the rise of the Rashtrakutas inthe middle of the 8th century eclipsed the Chalukyas of Badami before beingrevived by their descendants, the WesternChalukyas, in the late 10th century. These Western Chalukyas ruled fromKalyani (modern Basavakalyan) until the end of the 12thcentury.